Synthesis and Evaluation of Fluorous-Tagged and Polystyrene-Supported Precursors for Fluoro-benziodoxole - Racicot, Léanne; Valliant, John F.; Murphy, Graham K. (Synthesis, 2023)
Fluoro-benziodoxole, a fluorinated hypervalent iodine (HVI) reagent, has been prepared by fluoride exchange with fluorous- or polystyrene-based sulfonyloxy-benziodoxole precursors. Key to this strategy was the facile O-sulfonylation of a common hydroxy-benziodoxole precursor with sulfonyl chlorides, which enabled the easy synthesis and evaluation of previously unknown fluorous- or polystyrene-based fluoride exchange precursors. Fluorination of a fluorous-tagged iodane led to fluoro-benziodoxole in 67% yield in 10 minutes with TBAF, whereas fluoride exchange on the polystyrene-supported iodane led to the fluoro-benziodoxole in 82 ± 5% yield upon reacting with TBAF for 10 minutes.
Keywords: hypervalent iodine; fluorination; fluorous; solid-supported synthesis; synthetic methodology; radiofluorination